The Validation Of Reading Comprehension Test By Employing Rasch Model (A Study Case At English Department Of Papua University) - Mallipa, Imelda (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
This research investigated the validity of Reading Comprehension test that was taken from Longman complete course for the TOEFL test, Preparation for computer and paper test written by Debora Philips (2001), page 528 until page 537. Thirty-five undergraduate students of English Education major took part in this study. The result of the test are dichotomously scored and analysed by employing Rasch model with the application of winsteps software. The findings revealed that all items in Reading Comprehension Test were valid based on the criteria proposed by Boone et al. (2014). The test information function and the level of students’ ability was low. To get the optimal of test information function, the test should be administered to the students in medium ability. It is sugested to use this test to improve the reading comprehension of students with low level proficiency.